Peningkatan Minat Belajar Siswa pada Mata Pelajaran Bahasa Indonesia dengan Menggunakan Model Pembelajaran Contextual Teaching and Learning (CTL) di MTs Al-Falah Ajung Jember - Maulida, Zilfa; Susetyo, Agus Milu; Citraningrum, Dina Merdeka (Universitas Islam Sumatera Utara, 2025)
This study aims to analyze the impact of students' learning interest in the Indonesian language subject through the implementation of the Contextual Teaching and Learning (CTL) model. CTL is a teaching approach that connects the subject matter with students' real-life contexts, enhancing their engagement and comprehension of the material. This research employs a quantitative approach with a Classroom Action Research (CAR) design. The population consists of eighth-grade students at MTs Al-Falah Ajung Jember, with a sample of 14 students. A validated and reliable questionnaire was used as the primary instrument to measure students' learning interest. The findings reveal a significant difference in students' learning interest when taught using the CTL model compared to conventional methods. Students exposed to CTL demonstrated higher motivation and active participation in the learning process. The study successfully observed improvements in attendance, classroom participation, and overall academic performance. These results suggest that innovative and interactive teaching strategies like CTL can effectively enhance students’ learning interest. This research provides valuable insights for educators seeking to develop more engaging and effective instructional methods to foster student enthusiasm and participation in language learning.